The Effectiveness of Application of Regional Regulations Number 7 of 2015 concerning Non-Smoking Areas in Ogan Komering Ulu District Health Office - Heri Fachrizal; Eko Nurmardiansyah; Suwandi Sawandi (SOEPRA, 2018)
Effectiveness is a state that the extent to which shows the plan has been achieved. Smoking is a personal right of everyone, on the other hand, the need to respect and respect the rights of others to breathe fresh air free of cigarette smoke. When a smoking activity has violated a person's right to breathe clean air has begun to be neglected then the Government must be present to solve the problem. The negative impact of exposure to secondhand smoke is not only on active smokers but also has a major impact on people around who become passive smokers. Government Regulation NO. 7 The year 2015 has explained that the office is as a place of society or workers who come every day to work and later as one of the pioneers of the No Smoking Area. This study aims to determine the effectiveness of the application of local regulations at the Office of Health Office of OKU RegencyThe method in this research is sociological juridical, with analytical descriptive. Respondents are ten rooms and employees working in the room. The resource persons in this study were the head of OKU Regency Health Office and the sub-division HeadThe results of this study indicate regional regulation NO. 7 The year 2015 on Non-Smoking Areas that have been applied at the Office of Health Office OKU less effective. The results of this study also show that many employees found smoking in the area of No Smoking Area.